The enigma of ultraviolet radiation stress granules: Research challenges and new perspectives - Cabral, Alexandra J.; Costello, Danielle C.; Farny, Natalie G. (Frontiers in Molecular Biosciences, 2022)
Stress granules (SGs) are non-membrane bound cytoplasmic condensates that form in response to a variety of different stressors. Canonical SGs are thought to have a cytoprotective role, reallocating cellular resources during stress by activation of the integrated stress response (ISR) to inhibit translation and avoid apoptosis. However, different stresses result in compositionally distinct, non-canonical SG formation that is likely pro-apoptotic, though the exact function(s) of both SGs subtypes remain unclear. A unique non-canonical SG subtype is triggered upon exposure to ultraviolet (UV) radiation. While it is generally agreed that UV SGs are bona fide SGs due to their dependence upon the core SG nucleating protein Ras GTPase-activating protein-binding protein 1 (G3BP1), the localization of other key components of UV SGs are unknown or under debate. Further, the dynamics of UV SGs are not known, though unique properties such as cell cycle dependence have been observed. This Perspective compiles the available information on SG subtypes and on UV SGs in particular in an attempt to understand the formation, dynamics, and function of these mysterious stress-specific complexes. We identify key gaps in knowledge related to UV SGs, and examine the unique aspects of their formation. We propose that more thorough knowledge of the distinct properties of UV SGs will lead to new avenues of understanding of the function of SGs, as well as their roles in disease.